Vancomycin‐intermediate Staphylococcus aureus employs CcpA‐GlmS metabolism regulatory cascade to resist vancomycin - Huagang Peng; Yifan Rao; Weilong Shang; Yi Yang; Li Tan; Lu Liu; Zhen Hu; Yuting Wang; Xiaonan Huang; He Liu; Mengyang Li; Zuwen Guo; et al. (MedComm – Future Medicine)
Abstract Vancomycin (VAN)‐intermediate Staphylococcus aureus (VISA) is a critical cause of VAN treatment failure worldwide. Multiple genetic changes are reportedly associated with VISA formation, whereas VISA strains often present common phenotypes, such as reduced autolysis and thickened cell wall. However, how mutated genes lead to VISA common phenotypes remains unclear. Here, we show a metabolism regulatory cascade (CcpA‐GlmS), whereby mutated two‐component systems (TCSs) link to the common phenotypes of VISA. We found that ccpA deletion decreased VAN resistance in VISA strains with diverse genetic backgrounds. Metabolic alteration in VISA was associated with ccpA upregulation, which was directly controlled by TCSs WalKR and GraSR. RNA‐sequencing revealed the crucial roles of CcpA in changing the carbon flow and nitrogen flux of VISA to promote VAN resistance. A gate enzyme (GlmS) that drives carbon flow to the cell wall precursor biosynthesis was upregulated in VISA. CcpA directly controlled glmS expression. Blocking CcpA sensitized VISA strains to VAN treatment in vitro and in vivo. Overall, this work uncovers a link between the formation of VISA phenotypes and commonly mutated genes. Inhibition of CcpA‐GlmS cascade is a promising strategy to restore the therapeutic efficiency of VAN against VISA infections.